2018
DOI: 10.1177/1178221818805977
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cannabis Use Among Medical Students: A Systematic Review and Meta-analysis

Abstract: Objective:Cannabis is reported to be the most common illicit substance used among medical students; however, the number of related studies is limited and their results are not systematically reviewed. The aim of our study was to analyze the prevalence of lifetime and current use of cannabis among medical students worldwide.Methods:A systematic review and meta-analysis was performed with adherence to the PRISMA guidelines. The electronic databases PubMed, Scopus, and Cochrane library were searched for studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 48 publications
8
32
4
Order By: Relevance
“…Moreover, the rates of past year use were significantly higher for males for all types of illicit drugs, except synthetic cannabinoids and heroin (where numbers were very small overall). These findings lend support to previous studies from student populations that also report higher illicit drug use among males [e.g., (31)]. We found geographical differences in proportions of past year drug use, in which students in the Oslo area had either the highest or as high past year use across all substances compared with other areas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the rates of past year use were significantly higher for males for all types of illicit drugs, except synthetic cannabinoids and heroin (where numbers were very small overall). These findings lend support to previous studies from student populations that also report higher illicit drug use among males [e.g., (31)]. We found geographical differences in proportions of past year drug use, in which students in the Oslo area had either the highest or as high past year use across all substances compared with other areas.…”
Section: Discussionsupporting
confidence: 91%
“…Still, no research exists concerning the distribution of a wider array of illicit drug use among Norwegian University and college students, something which needs to be addressed. Moreover, prevalence rates of illicit drug use tend to vary substantially across countries in the general adolescent ( 29 ), adult ( 30 ), and student population ( 31 ), and rates of drug use vary over time even within a given country [e.g., ( 32 )]. In addition, illicit drug use may vary considerably across geographical areas within a country [e.g., ( 19 )].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the observed trend is towards similar consumption rates for all substances in both genders [30]. Despite the increasing prevalence of recreational cannabis use among the young population [40] and medical students [41], mainly for its rewarding effects [42,43], the use of cannabinoids among students might also be explained by their anxiolytic, antidepressant, and sleep-promoting effects [44] as a means to mitigate the effects of exposure to different stressors and burnout [11,45,46]. The use of both alcohol and cannabis may affect the current academic performance of students [47], and they may also contribute to misjudgments and misperceptions as future nurses towards patients with substance use disorders [48].…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with the findings of previously published studies. For instance, in a recent meta-analysis of 25 studies that had investigated past-month cannabis use in medical students, Papazisis et al found an estimated prevalence of 8.8% [ 4 ]. Although published results are rather heterogeneous, when considering studies assessing larger cohorts, the data nevertheless seems in keeping with our results [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…While one might expect that the prevalence would be high during late adolescence and early adulthood, there are studies indicating that the recreational use of cannabis is not limited to this demographic. For instance, a 2018 systematic review on cannabis use by medical students reported a past-month use of cannabis by 8.8% of students [ 4 ]. It has been proposed that the rate of cannabis use among medical students is associated with exposure to diverse stressors and an attempt to prevent burnout [ 5 ].…”
Section: Introductionmentioning
confidence: 99%